The flow of understanding and variety of communication behaviors religious moderation communities on the slopes of Merapi volcano - Mukti Ali; Hasan Maftuh; Muhamad Mustholiq Alwi (Jurnal Ilmu Dakwah, 2022)
Purpose - People who live on the slopes of Merapi Volcano apply religious moderation behavior by respecting traditions and other thoughts. The purpose of this study was to find out the tradition and communication of religious moderation in the community on the slopes of Merapi Volcano.Method - The research uses the descriptive-qualitative method. The research location took place in the Srumbung sub-district, Magelang district. Data was collected through interviews, observation, and documentation. Informants in this study were young people and community leaders in the village.Result - The results of this study indicate that there are two characteristics of the community thought traditions in the implementation of religious moderation, namely people who can apply this concept well and thoroughly, and there are people who are against the concept of religious moderation, who tend to be intolerant towards diversity and differences of opinion and thoughts.Implication - The contribution of this study on religious moderation has become a barrier to critical thinking discourses that are currently developing. Religious moderation is an alternative solution to the current trend of thought, such as radical, liberal, and even fundamental ways of thinking.Originality - This study looks at the traditions of thought developing in the community. Furthermore, this research aims to look at the communication of religious moderation of da'wah in society. The sociological perspective as a research approach is expected to be able to find social facts found in society.***Tujuan - Masyarakat yang tinggal di lereng Gunung Merapi menerapkan perilaku moderasi beragama dengan menghargai tradisi dan pemikiran lain. Tujuan dari penelitian ini adalah untuk mengetahui tradisi dan komunikasi moderasi beragama pada masyarakat di lereng Gunung Merapi.Metode - Penelitian ini menggunakan metode deskriptif-kualitatif. Lokasi penelitian berlangsung di Kecamatan Srumbung Kabupaten Magelang. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Informan dalam penelitian ini adalah para pemuda dan tokoh masyarakat di desa tersebut.Hasil - Hasil penelitian ini menunjukkan bahwa terdapat dua ciri tradisi pemikiran masyarakat dalam penerapan moderasi beragama, yaitu masyarakat yang dapat menerapkan konsep ini dengan baik dan tuntas, dan terdapat masyarakat yang menentang konsep moderasi beragama, yang cenderung tidak toleran terhadap keragaman dan perbedaan pendapat dan pemikiran.Implikasi - Kontribusi kajian tentang moderasi beragama ini menjadi penghambat wacana berpikir kritis yang berkembang saat ini. Moderasi beragama merupakan solusi alternatif dari pola pikir yang berkembang saat ini, seperti cara berpikir radikal, liberal, bahkan fundamental.Orisinalitas - Kajian ini melihat tradisi pemikiran yang berkembang di masyarakat. Selanjutnya, penelitian ini bertujuan untuk melihat komunikasi moderasi dakwah dakwah di masyarakat. Perspektif sosiologis sebagai pendekatan penelitian diharapkan mampu menemukan fakta-fakta sosial yang ditemukan di masyarakat.